Pengaruh Formula EDAMTIKA terhadap Tingkat Konsumsi Makro dan Berat Badan Lansia di Tresna Werdha Jember - Agatha Widiyawati; Ardiyani, Rahma Aisyah; Pratiwi, Niken; Susindra, Yoswenita (Puslitbang Sinergis Asa Professional, 2024)
An elderly person is someone who is 60 years or older. One of the nutritional problems often encountered in the elderly is thin nutritional status. Elderly people with thin nutritional status need to be given additional food in the form of high-calorie foods that are easy to digest. EDAMTIKA food formula is a powdered food formula which has the basic ingredient of edamame and is high in calories. The aim of this research was to determine the effect of giving the EDAMTIKA food formula on the level of consumption of macronutrients (energy, protein, fat and carbohydrates) and body weight in elderly people with underweight nutritional status at UPT. Pelayanan Sosial Tresna Werdha Jember Tresna Werdha Jember. This research uses true experimental designs research with a cross-over design. The subjects of this study were 19 elderly people who met the inclusion criteria. Elderly respondents were given 200 ml of the EDAMTIKA food formula 2 times a day for 7 days. Based on the Wilcoxon test, there is an effect of giving the EDAMTIKA food formula on the level of energy consumption (p=0.021), protein (p=0.000), fat (p=0.046), carbohydrates (p=0.000) and body weight (p=0.000) in the elderly. lean nutrition. Based on the Wilcoxon test, there was no effect without giving the EDAMTIKA food formula on the level of energy consumption (p=0.064), protein (p=0.053), fat (p=0.083), carbohydrates (p=0.727), and body weight (p=0.222) in the elderly thin nutritional status. Based on the Mann-Whitney test, there were differences in levels of energy consumption (p=0.000), protein (p=0.000), fat (p=0.000), and carbohydrates (p=0.002) in the treatment group and the control group. Based on the Mann-Whitney test, there was no difference in body weight (p=0.770) in the treatment group and the control group.